2023
DOI: 10.3920/cep220039
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of various exercises in the management of upper crossed syndrome

Abstract: Upper crossed syndrome (UCS) is characterised by distortion or imbalances of various muscles that put tension on the nearby tendons, bones, and joints leads to muscle weakness, tiredness, sore shoulder blades, headache and limitation of movements. The rationale of the present study was to evaluate the efficacy of various exercises (McKenzie and TheraBand exercises) on posture, pain and strength in patients suffering with upper crossed syndrome. The participants were randomly allocated into two groups: Group 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Physiotherapy plays a vital role in treating UCS. It seeks to address postural imbalances, strengthen weak muscles, reduce discomfort, increase range of motion, and provide patients with the information and resources they need to maintain good posture and stop the illness from returning [10]. The present study identified the condition of UCS through kinematic analysis using Xsens and concentrated on neck, trunk, lumbopelvic complex, and arm swing components.…”
Section: Introductionmentioning
confidence: 99%
“…Physiotherapy plays a vital role in treating UCS. It seeks to address postural imbalances, strengthen weak muscles, reduce discomfort, increase range of motion, and provide patients with the information and resources they need to maintain good posture and stop the illness from returning [10]. The present study identified the condition of UCS through kinematic analysis using Xsens and concentrated on neck, trunk, lumbopelvic complex, and arm swing components.…”
Section: Introductionmentioning
confidence: 99%